The Use of Self Regulated Learning in Increasing Student Learning Effectiveness - Rita, Costa; Geraldo, Tostes; Marilia, Busatto; Federica, Keijzer; Linty, Mathieu (Al-Hijr: Journal of Adulearn World, 2024)
As time goes by, education will continue to experience difficulties, therefore students cannot only wait for the lessons given by the teacher, self-regulated learning is needed to increase student effectiveness. So that students quickly understand the lesson and the teacher does not have difficulty explaining the material that will be presented. Purpose of the research This is to increase student learning effectiveness by using self-regulated learning.Method usedby researchers in conducting this research areQuantitative, data obtained through distributing online questionnaires using Google Forms.Results of this researchshows that there is an increase in student learning effectiveness through the use of self-regulated learning.Conclusion of this researchis to increase discipline and independence of students who cannot be controlled. Therefore, self-regulated learning is needed to facilitate understanding of learning material.Limitations in researchThis researcher only conducted research online so the data obtained was less relevant. This research also recommendsto future researchers so that it becomes a challenge to use self-regulated learning in increasing student learning effectiveness.